TOPoS: V. Abundance ratios in a sample of very metal-poor turn-off stars - François, Patrick; Caffau, Elisabetta; Christlieb, Norbert; Klessen, Ralf S.; Koch-Hansen, Andreas; Ludwig, Hans-Günter (Astronomy and astrophysics, 2018)
Extremely metal-poor stars are keys to understand the early evolution of our Galaxy. The ESO large programme TOPoS has been tailored to analyse a new set of metal-poor turn-off stars, whereas most of the previously known extremely metal-poor stars are giant stars.Aims. Sixty five turn-off stars (preselected from SDSS spectra) have been observed with the X-shooter spectrograph at the ESO VLT Unit Telescope 2, to derive accurate and detailed abundances of magnesium, silicon, calcium, iron, strontium and barium.Methods. We analysed medium-resolution spectra (R ≃ 10 000) obtained with the ESO X-shooter spectrograph and computed the abundances of several α and neutron-capture elements using standard one-dimensional local thermodynamic equilibrium (1D LTE) model atmospheres.Results. Our results confirms the super-solar [Mg/Fe] and [Ca/Fe] ratios in metal-poor turn-off stars as observed in metal-poor giant stars. We found a significant spread of the [α/Fe] ratios with several stars showing subsolar [Ca/Fe] ratios. We could measure the abundance of strontium in 12 stars of the sample, leading to abundance ratios [Sr/Fe] around the Solar value. We detected barium in two stars of the sample. One of the stars (SDSS J114424−004658) shows both very high [Ba/Fe] and [Sr/Fe] abundance ratios (>1 dex).
Gesehen am 16.10.2020